The psychology book : big ideas simply explained. - Collin, Catherine (Clinical psychologist) (DK Publishing, 2015)
The Psychology Book clearly and simply explains more than one hundred groundbreaking ideas of the great scientists and thinkers who contributed to the development of psychological thought. Using easy-to-follow graphics and artworks, succinct quotations, and thoroughly accessible text, The Psychology Book makes abstract concepts concrete. The Psychology Book includes innovative ideas from ancient and medieval thinkers ranging from Galen and RenE Descartes to the leaders of psychotherapy, such as Sigmund Freud and Abraham Maslow. The voices that continue to shape modern psychology, from Nico Fridja to David Rosenhan, are also included, giving anyone with an interest in psychology an essential resource to psychological thinking and history.